KONDISI EKONOMI MASYARAKAT SEKITAR TPA WISATA EDUKASI TALANGANGGUNG DI DESA TALANGANGUNG KECAMATAN KEPANJEN KABUPATEN MALANG - Tamami, Rofidah; Ayu, Sulistia Ningrum; Syamsiah, Nur; Munadifah, Lailatul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Urban is identical to the high consumptive behavior of the people who will then leave a lot of garbage too. The uncontrolled volume of waste will certainly disrupt the survival of the people who live in that place. Waste itself can be divided into two categories, namely organic waste and inorganic waste, which means that there is still a possibility to be reprocessed. So that the garbage does not interfere with the survival of the community, a waste collection facility or a waste bank is made which will later be collected again at the Final Disposal Site. Research conducted using qualitative methods with a descriptive approach. This research was conducted with the aim to find out how much influence the existence of the Talangagung Kepanjen Final Disposal on the surrounding community's economy. From the results of the study, it was found that the Talangagung Landfill is in addition to being a landfill, as well as an educational tourism site. Besides Talangagung Landfill has economic potential that can help the economy of the surrounding residents.Keywords: economy; final disposal site; educational tourism